PENGARUH KOMPENSASI, KEPEMILIKAN MANAJERIAL, DIVERSIFIKASI PERUSAHAAN DAN UKURAN KAP TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 (Universitas Islam Malang, 2020)
This study aims to analyze the effect of compensation, managerial ownership, company diversification, and KAP size on earnings management. Hypothesis testing used Regression Analysis. The research used secondary data from www.idx.com. This study used 49 manufacturing companies that have been selected through purposive method for three years. Hypothesis testing used Regression Analysis. Simultaneously bonus compensation, managerial ownership, corporate diversification and size of KAP have a significant influence on profit management. Partial compensation of bonuses, managerial and diversified ownership of the company has no significant influence on profit management Keywords: compensation, managerial ownership, company diversification, KAP size, and earnings management